2019
DOI: 10.21608/bvmj.2019.79648
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal residues and health risk assessment in raw milk and dairy products with a trail for removal of copper residues.

Abstract: A B S T R A C TThis study was conducted to determine the residues of Lead (Pb), Cadmium (Cd), and Copper (Cu) in different types of raw milk and dairy products, and to estimate the dietary intake of such metals, as well as to evaluate the potential health hazards of these metals to peoplethrough consuming milk and dairy products. On the other hand, we made a trial to remove copper residues using the adsorption properties of the resin. Therefore, a total of 120 random samples of milk and dairy products, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A number of techniques are used to quantified heavy metals in the aqueous phase which related to the desired level of detection and the specific analyte. Our finding showed that from 48 included articles, 15 techniques were used to measure heavy metals in pasteurized and sterilized milk include; Atomic Absorption Spectroscopy (AAS)(15:31.3%) [ 11 , 18 , 33 , 40 43 , 50 , 51 , 53 , 55 57 , 61 , 67 ], Microwave Plasma–Atomic Emission Spectrophotometer(MP-AES)(1:2.1%) (21),Metrohm 797 VA Computrace(1:2.1%), Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES)(2:4.15%) [ 25 , 32 ], Graphite Furnace Atomic Absorption Spectroscopy(GFAAS) (2:4.15%) [ 5 , 35 ], Flame Atomic Absorption Spectrophotometer (FAAS)(3:6.3%) [ 39 , 46 , 64 ], Inductively Coupled Plasma-Mass Spectrometry (ICP-MS)(7:15%) [ 34 , 38 , 44 , 45 , 49 , 52 , 65 ], Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES)(4:8.5%) [ 4 , 22 , 37 , 62 ], polarography apparatus(1:2.1%) [ 24 ], voltammeter(1:2.1%) [ 20 ], Laser Induced Breakdown Spectroscopy (LIBS)(1:2.1%) [ 48 ], Inductively Coupled Plasma Sector Field Mass Spectrometry (ICP-SFMS)(1:2.1%) [ 36 ], Anodic Stripping Voltammetry (ASV)(1:2.1%) [ 54 ], Electrothermal Atomic Absorption Spectrophotometer(ET-AAS)(2:4.15%) [ 58 , 66 ] and Metrohm 746 VA trace(1:2.1%) [ 59 ], and 5 studies(5:10.5) [ 3 , 23 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of techniques are used to quantified heavy metals in the aqueous phase which related to the desired level of detection and the specific analyte. Our finding showed that from 48 included articles, 15 techniques were used to measure heavy metals in pasteurized and sterilized milk include; Atomic Absorption Spectroscopy (AAS)(15:31.3%) [ 11 , 18 , 33 , 40 43 , 50 , 51 , 53 , 55 57 , 61 , 67 ], Microwave Plasma–Atomic Emission Spectrophotometer(MP-AES)(1:2.1%) (21),Metrohm 797 VA Computrace(1:2.1%), Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES)(2:4.15%) [ 25 , 32 ], Graphite Furnace Atomic Absorption Spectroscopy(GFAAS) (2:4.15%) [ 5 , 35 ], Flame Atomic Absorption Spectrophotometer (FAAS)(3:6.3%) [ 39 , 46 , 64 ], Inductively Coupled Plasma-Mass Spectrometry (ICP-MS)(7:15%) [ 34 , 38 , 44 , 45 , 49 , 52 , 65 ], Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES)(4:8.5%) [ 4 , 22 , 37 , 62 ], polarography apparatus(1:2.1%) [ 24 ], voltammeter(1:2.1%) [ 20 ], Laser Induced Breakdown Spectroscopy (LIBS)(1:2.1%) [ 48 ], Inductively Coupled Plasma Sector Field Mass Spectrometry (ICP-SFMS)(1:2.1%) [ 36 ], Anodic Stripping Voltammetry (ASV)(1:2.1%) [ 54 ], Electrothermal Atomic Absorption Spectrophotometer(ET-AAS)(2:4.15%) [ 58 , 66 ] and Metrohm 746 VA trace(1:2.1%) [ 59 ], and 5 studies(5:10.5) [ 3 , 23 , …”
Section: Resultsmentioning
confidence: 99%
“…A total of 48 potentially relevant articles with data on 981 pasteurized and sterilized milk were included in the systematic review. All data were collected from 17 different countries including Iran (13:27%) [ 3 , 5 , 12 , 20 , 23 , 24 , 32 , 36 , 41 , 43 , 48 , 50 , 62 ], Pakistan (6:12.5%) [ 4 , 11 , 42 , 55 , 58 , 63 ], Egypt(5:10%) [ 18 , 40 , 45 , 53 , 56 ], and Brazil (4:8%) [ 22 , 46 , 54 , 64 ] represented the highest number of studies, and the sample size was varied from 5 to 90. Based on results, the first study was conducted in 1993, and 70% of the studies were done in the past five years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IMAC HP resin was described for the removal of copper ions (76.89%). 92 Tetracycline, oxytetracycline, chlortetracycline, and doxycycline have been removed by adsorption on a molecularly imprinted polymer, achieving 81.83, 95.47, 96.44, and 93.25% removal, respectively. 239 A photocatalytic-fluorescent polymer, produced from graphene oxide and bismuth phosphate with molecular magnetic imprinting, allowed ciprofloxacin's complete degradation.…”
Section: Alternative Methods For the Treatment Of Cow's Milkmentioning
confidence: 99%